ATTITUDES, SATISFACTION, AND ASSOCIATED FACTORS WITH THE PURCHASE OF SWEET SOY SAUCE BY FOOD SELLER IN THE OLD MARKET CULINARY OF TANGERANG - Zefanya, Prillia Mberru; Indriani, Yaktiworo; Adawiyah, Rabiatul (Jurusan Agribisnis, Fakultas Pertanian, Universitas Siliwangi, 2025)
This research aims to analyze attitudes,osatisfaction, and factors related to sweet soy sauce purchases. The study was conductedoby survey method in which location was determined purposively at the Old Market Culinary Tourism in Tangerang. The number of respondents was 52 food seller consisting of 37 seller who use Benteng SH brand Soy Sauce and 15 seller who use other brands. Research data were analyzed by Fishbein Multiattribute Model to determine the attitudes of food seller, Customer Satisfaction Index (CSI) to determine food seller satisfaction towards Benteng SH Brand Soy Sauce, and correlation of Spearman Rank to determine factors related to the number of sweet soy sauce purchases. The result showed that most of the seller were male (76.9%) with the highest education level of high school (30.7%). Most seller (56%) sold non-soup foods with revenues of Rp5,000,000.00 per week. The results showed that the attitude of food seller towards multiattributes of Benteng SH Brand Soy Sauce was good with Ao value of 175.21. The level of satisfaction of food seller who use Benteng SH Brand Soy Sauce was 93.64%, categorized as very satisfied. The sweet soy sauce purchase were negatively related to price and positively related to color, ease of access, and location of purchase, all were in the less-related category.